Economic geographies of religious institutions - Corah, James (2010)
The Christian Church is one of the oldest institutions in the UK. Furthermore, the Church is an important economic actor in the British economy, with the current Church of England holding investment assets of approximately £8billion. In addition it provides the largest amount of explicitly religious spaces, through its network of Churches, in the nation. However, despite a recent resurgence of interest from geographers in religion, through the Geography of Religion discourse, the Christian Church is, and has remained, an understudied institution. In contrast, I will argue that the particular characteristics of the faith make it an ideal institution for study. By investigating the Church I will integrate the previously disparate literatures of the Geography of Religion and Economic Geography to identify how the spaces of Christian religious institutions, such as the Parish Church, continue to exist in the capitalist economic system of the UK. To this end the thesis will adopt an economic institutionalist perspective to understanding religious bodies; using the case studies of The Church of England, The Baptist Union, and The Assemblies of God to investigate the process of institutional reproduction. In addition to providing an overview of how religious institutions are reproduced the thesis will make a further two contributions to Geography. First, it will investigate how Christianity and capitalism interrelates. In so doing I will argue that, whilst geographers have traditionally argued that institutions influence the practices of capitalism, this is a two-way process as the economic imperative of reproduction entails that capitalism itself also alters the properties of religious institutions. Second, the thesis will provide an investigation of the internal properties of institutions to argue that, rather than being a cohesive body, religious institutions are an assemblage of a number of linked networks. This has a severe impact on the process of institutional reproduction as finance and resources do not flow freely around the institution to where they are needed.